Interstratified Illite/Montmorillonite in Kamojang Geothermal Field, Indonesia - Yudiantoro, D. F.; suparka, E.; Yuwono, S.; Takashima, I.; Ishiyama, D.; Kamah, Y.; Hutabarat, J. (Indonesian Journal on Geoscience, 2013)
DOI:Â 10.17014/ijog.v8i4.167Kamojang geothermal field located in West Java Province, falls under the Pangkalan Subregency, Bandung Regency. The researched area is a geothermal field located in the Quaternary volcanic caldera system of about 0.452 to 1.2 Ma. The volcanic activity generated hydrothermal fluids, interacting with rocks producing mineral alteration. The minerals formed in the areas of research are interstratified illite/montmorillonite (I/M). Analyses to identify interstratified I/M have been performed by X-ray diffraction using ethylene glycol, while the determination of the type and percentage of interstratified I/M was based on the calculation method of Watanabe. The methodology was applied on core and cutting samples from Wells KMJ-8, 9, 11, 13, 16, 23, 49, 51, and 54. The result of analysis of the samples shows that the type of clay is interstratified illite/montmorillonite and the minerals are formed at temperatures ranging from 180 to 220Â° C. The type of interstratified I/M in the studied area is S = 0 and S = 1. The percentage of illite type S = 0 is between 20 - 35% illite, whereas type S = 1 has about 45 - 72% illite. Along with the increasing depth, the percentage of illite is getting greater. This is consistent with the vertical distribution of temperature which increases according to the depth. This correlation results in an interpretation that the upflow zone of the geothermal reservoir is located in the centre of the Kamojang geothermal field.